2016
DOI: 10.1590/1678-4324-2016150116
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effect of Oleuropein from Olea europaea Leaf against Alloxan Induced Type 1 Diabetic in Rats

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…On the other hand Table 9 showed that the Granulocytes (GRA) of normal nutrition of rats, was 38.0% while after supplementation with olive pomace attribution 2.5, 5, 7.5 and 10%, of nutrition of rats on (GRA) they were 38.5, 39.0 and 39.7%, respectively. This results agreed with Mahmoud et al (2013), Nandakumaran et al (2014) and Nadir et al (2016) who found the effects of oleuropein on hematological analysis including (RBCs, Hb, PCV and PLTs) in plasma of experimental rats, which were 7.44(x10 6 /μL), 14.2(g/dl), 44.25% and 434.00(x10 3 /μL), at treatment 10mg/kg, respectively compared to those of normal control rats, which were 6.75(x106/μL), 12.82(g/dl), 40.35% and 456.13(x103/μL), at treatment 10mg/ kg, respectively.…”
Section: Data Insupporting
confidence: 93%
“…On the other hand Table 9 showed that the Granulocytes (GRA) of normal nutrition of rats, was 38.0% while after supplementation with olive pomace attribution 2.5, 5, 7.5 and 10%, of nutrition of rats on (GRA) they were 38.5, 39.0 and 39.7%, respectively. This results agreed with Mahmoud et al (2013), Nandakumaran et al (2014) and Nadir et al (2016) who found the effects of oleuropein on hematological analysis including (RBCs, Hb, PCV and PLTs) in plasma of experimental rats, which were 7.44(x10 6 /μL), 14.2(g/dl), 44.25% and 434.00(x10 3 /μL), at treatment 10mg/kg, respectively compared to those of normal control rats, which were 6.75(x106/μL), 12.82(g/dl), 40.35% and 456.13(x103/μL), at treatment 10mg/ kg, respectively.…”
Section: Data Insupporting
confidence: 93%
“…In addition, it seems that hyperglycemia is accompanied by an increase in free radicals in the body. Furthermore, food antioxidants are effective in reducing the complex effects resulting from oxidative stress of diabetes type I (20). Chronic hyperglycemia induces carbonyl stress, which in turn increases lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…A negative correlation was noticed between GSH and hyperglycemia, which means that rising serum glucose reduced the antioxidant capacity (Qadir et al, 2016). There is an inverse correlation which has been revealed among glucose level and enzymatic and non-enzymatic antioxidants (Qadir et al, 2016).…”
Section: Changes In Mda and Gsh Of Normal And Diabetic Ratsmentioning
confidence: 93%
“…In fact, oleuropein represented more than 50% of the total recognized compounds in olive leaves,followed by hydroxytyrosol, then many other phenolics (Charoenprasert and Mitchell, 2012). Oleuropein inhibitted the activities of free radicals and inhibitted oxidative stress in diabetic-induced rats (Qadir et al, 2016). The potent antioxidant activity of olive leaf extract could be attributed to its high total polyphenolic compound content, and oleuropein (Salah et al, 2012).…”
Section: Dpph Free Radical Scavenging Activity Of Olive Leaf Extractmentioning
confidence: 99%
See 1 more Smart Citation